Implementing the Team Assisted Individualization Learning Model to Enhance Anecdotal Text Writing Skills in Grade X Students - Junifer Siregar; Meliana Br Gultom (STAI Hubbulwathan Duri, 2025)
This study aims to investigate the effectiveness of the Team Assisted Individualization (TAI) learning model in improving Grade X students' skills in writing anecdotal texts. Writing is a fundamental language skill that remains challenging for many students, particularly in crafting anecdotal texts, which require creativity, structure, and a clear narrative. This research was conducted at SMA Swasta Teladan Pematangsiantar during the 2022/2023 academic year, involving 70 Grade X students selected through cluster sampling. A pre-experimental one-group pretest-posttest design was employed. Students were assessed using a written test administered before and after the implementation of the TAI model. Data were analyzed using a paired sample t-test at a 0.05 significance level. The results showed a substantial improvement in students’ writing performance. The average pre-test score was 44.22, categorized as low, while the average post-test score increased to 77.88, indicating a good level of writing proficiency. The statistical analysis yielded a t-value of -28.01, which exceeded the critical value (t-table = 1.996), leading to the rejection of the null hypothesis. These findings indicate that the TAI learning model significantly enhances students’ ability to write anecdotal texts. The collaborative and individualized nature of the TAI model supports active student engagement, idea development, and writing fluency. This study recommends the integration of the TAI model into Indonesian language instruction to foster students' writing competence and motivation.